In planta efficacy of local Trichoderma isolates and selected commercial biological agents against Ganoderma boninense in oil palm - Jumiati Asis; Nur Aainaa Hasbullah; Mohamadu Boyie Jalloh; Palanivell Perumal; Peter Mojiun; Mohd Rashid Mohd Rakib (Malaysian Palm Oil Board, 2025)
Trichoderma species are well-known biological control agents with significant antagonistic activity against various fungal phytopathogens. This study evaluated the in planta efficacy of local Trichoderma isolates (Trichoderma virens and Trichoderma asperellum) in comparison to commercial biological control agent (BCA) products in controlling Ganoderma disease in oil palm seedlings. The local Trichoderma isolates were applied either singly or as a mixture to the soils of both transplanted and Ganoderma-inoculated oil palm seedlings. Additionally, two commercial BCA products were tested as benchmarks, with a negative and a positive control. It was found that the local Trichoderma isolate, either applied singly or as a mixture, could reduce disease by 41.82%-57.73%, and be on par with the commercial BCA products. Untreated positive control showed a significant loss in physiological integrity, in terms of chlorophyll content, plant height, bole diameter, and the number of fronds, due to the G. boninense infection, meanwhile, the treated seedlings with local Trichoderma isolates and commercial BCAs were able to resist the infection significantly to a certain degree. These isolates are promising BCAs for the future management of G. boninense in oil palm.